Protective Mechanisms of Quercetin Against Myocardial Ischemia Reperfusion Injury - Zhang, Yu-Min; Zhang, Zhen-Ye; Wang, Ru-Xing (Frontiers in Physiology, 2020)
More attentions have been paid on Quercetin and its ramifications in recent years and they may ameliorate the ischemia/reperfusion injury. Quercetin can alleviate the oxidative stress injury, through inhibiting NADPH oxidase and xanthine oxidase, blocking the Fenton reaction and scavenging the reactive oxygen species. Quercetin also possesses the potentials of anti-inflammation and anti-apoptosis, and it can reduce the stimulation of inflammatory factor and decrease the cell apoptosis. Moreover, it can induce vasodilative effects through inhibition of endothelin-1 receptors, enhancement the stimulation of NO and activation of the large-conductance calcium-activated potassium channels. Finally, it can also antagonize the calcium overload. These multifaceted activities of Quercetin make it a possible therapeutic alternative to exempt from the ischemia / reperfusion injury.